Creation of an Additional Glycosylation Site as a Mechanism for Type I Antithrombin Deficiency - Fitches, Alison C.; Lewandowski, Krzysztof; Olds, Robin J. (Thrombosis and Haemostasis, 2001)
We report the identification of a new mutation resulting in type I antithrombin (AT) deficiency and the mechanism by which the deficiency arose. The single base substitution of G to A at nucleotide 2709 was identified in a proband with a family history of venous thrombosis. The mutation results in a substitution of 82 Ser by Asn, creating a new glycosylation site. Expression studies were then carried out, to confirm Asn-linked glycosylation occurred at this consensus site and that this resulted in the AT deficient phenotype. Cell-free translations using rabbit reticulocyte lysate in the presence of microsomes demonstrated that the 82 Asn variant was post-translationally processed efficiently. The 82 Asn variant protein was of a higher molecular weight than normal AT, consistent with the addition of a fifth glycan chain. Incubation of translation product with endoglycosidase H, confirmed that the higher molecular weight product had resulted from additional carbohydrate. Expression of the 82 Asn variant in COS-7 cells resulted in intracellular accumulation, with a low level of secretion of the protein into culture supernatant, consistent with type I AT deficiency. The addition of an extra carbohydrate side chain to residue 82 of antithrombin may block post-translational folding, trapping the variant intracellulary.
Keywords: Antithrombin; glycosylation; venous thrombosis